Excitation‐Dependent Long Afterglow Room‐Temperature Phosphorescence Material Activated by Doping Boric Acid Matrix - Deng, Junjie; Guan, Zhihao; Fu, Donglei; Zheng, Yuewei; Chen, Zhengjie; Li, Houbin; Liu, Xinghai (Advanced optical materials, 2023)
Room‐temperature phosphorescence (RTP) materials are normally prepared by doping guest materials into space‐limited host materials to inhibit nonradiative decay. This work aims to prepare a long afterglow excitation‐dependent emission RTP material by doping a small amount of 4‐carboxyphenylboronic acid into the boric acid matrix, followed by heat‐treating. The calculation of density functional theory shows that the electron cloud distribution and electron transfer trend of the selected material reduces the energy requirement to excite the RTP properties of the obtained materials. The obtained RTP materials can be excited by UV light at 310 and 365 nm for dark blue and green phosphorescence emission, respectively. The results demonstrate the long phosphorescence lifetimes of 1.97 and 0.62 s and the high absolute photoluminescence quantum yields of 17.4% and 15.6%. These results show that the obtained RTP materials have potential prospects as information coding and phosphorescent anti‐counterfeiting. A long afterglow excitation‐dependent emission room‐temperature phosphorescence material is reported, emitting dark blue and green phosphorescence upon UV excitation at 310 and 365 nm with lifetimes of 1.97 and 0.62 s, respectively, and absolute photoluminescence quantum yields of 17.4% and 15.6%, with potential promise for information encoding and phosphorescence anti‐counterfeiting.